Mineralogia, causas de cor e gênese da titanita do município de Capelinha (Minas Gerais) - Eder Luiz Tolentino Junior (2017)
Titanite is a mineral much appreciated worldwide, especially the colors: green, yelow-green and orange. In Brazil, its main deposits are in the northern Minas Gerais (MG), still little is known in geological and mineralogical terms, and generally considered as an integral part of the Eastern Brazilian Pegmatite Province. The purpose of this work was to study the main deposits located in the surroundings of the city of Capelinha (MG), known as Campo do Boa and Fanadinho, in order to better understand its geological, mineralogical, chemical and also the color causes of titanite. These deposits are hosted in a basic metavulcanic shale, mainly composed of albite, epitote, actinolite, titanite and quartz, related to the Capelinha Formation, of the Macaúbas Group, of Tonic age. The veins have thicknesses ranging from a few centimeters up to 4 m; they are formed primarily of feldspars (albite and adularia), sometimes kaolinized, where drusas of titanite and epidote are locally present. Other important minerals in these veins, though uncommon, are apatite, ilmenite and actinolite. Samples of titanite and other associated minerals, such as quartz and feldspars, were collected to be analyzed by electron microprobe (EM), X-ray diffraction, X-ray fluorescence, electron paramagnetic resonance (EPR), optical absorption and fluid inclusions. The analysis by EM indicated a significant presence of Al2O3, Fe2O3 and H2O, probably substitutional. These results were used to compare Capelinha titanites with samples from other Brazilian and world deposits and also served as a basis for EPR and optical absorption analysis. Through these analyses, the presence of iron in the titanite was proven and it was verified that the ion Fe3+ is the cause of the yellow-green color in the mineral. The results of X-ray diffraction and fluorescence confirmed the predominance of albite, epidote, adularia and quartz in the deposits, including the almost constant presence of titanium in them. Finally, through the analysis of fluid inclusions, it was possible to relate the hydrothermal fluid trapping temperature, between 300 and 400 ° C, with the petrographic studies of the metamorphic conditions in the Capelinha region. Thus, it is believed that the formation of these inclusions is of similar age to the metamorphic process submitted to the regional rocks of amphibolite facies and occurred in ± 570 Ma, probably derived from hydrothermalism at the end of this process. The deposits of titanite and epidote, essentially associated with the alteration of the basic rocks, do not have any relation with the newer pegmatitic acid deposits (510-480 Ma) included in the Eastern Brazilian Pegmatite Province.